2017
DOI: 10.1080/03019233.2017.1410966
|View full text |Cite
|
Sign up to set email alerts
|

Spatial vibration characteristics of six-high cold strip rolling mills

Abstract: The vibration characteristic technical indexes of six-high cold strip rolling mills are not given, and thus the chatter vibrations cannot be predicted and prevented. The strip rolling mills can be divided into the non-statically determinate and statically determinate mills according to the statically determinate theory of mechanism. This statically determinate characteristic of the mill does not be distinguished in the traditional mill vibration analysis. In this paper, for these two distinct mill configuratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the metallurgical industry, the rolling mill represents a core piece of equipment. However, it has been found that there are always some parameter changes or disturbance factors during the rolling process, which may induce vibration in the rolling mill [1,2]. This may even cause the load roll system to produce vertical vibration with large amplitude, leading to production accidents such as steel-heaping, strip breakage, component damage and so on [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In the metallurgical industry, the rolling mill represents a core piece of equipment. However, it has been found that there are always some parameter changes or disturbance factors during the rolling process, which may induce vibration in the rolling mill [1,2]. This may even cause the load roll system to produce vertical vibration with large amplitude, leading to production accidents such as steel-heaping, strip breakage, component damage and so on [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [5] and Wu et al [6] developed a theoretical model for mixed lubrication and analysed the effects of surface roughness, rolling speed, rolling reduction, and rolling oil viscosity on oil film thickness in the deformation zone. Fujita et al [7], Wei et al [8], and Zheng et al [9] improved the vibration stability by controlling the lubricity in high speed cold rolling. Bai et al [10] developed an optimization technology of emulsion flow to minimize the overall fluctuation of rolling pressure during speed acceleration and deceleration in the rolling process.…”
Section: Introductionmentioning
confidence: 99%
“…[8], and Zheng et al. [9] improved the vibration stability by controlling the lubricity in high speed cold rolling. Bai et al.…”
Section: Introductionmentioning
confidence: 99%